How does physical education influence university students’ psychological health? An analysis from the dual perspectives of social support and exercise behavior - Xu Han; Haozhen Li; Ling Niu (Frontiers in Psychology)
ObjectivePhysical education, as a central component of educational systems, plays a unique role in enhancing the psychological well-being of university students. This study investigates the impacts of physical education on students’ mental health and examines the mediating roles of social support and exercise behavior.MethodologyA cross-sectional survey was conducted using the Physical Education Satisfaction Scale, SCL-90, the Social Support Questionnaire, and the International Physical Activity Questionnaire. A total of 1,437 university students were assessed.ResultsThe research found a positive correlation between physical education at universities and students’ mental health, with a direct significant effect (β = 0.622, p < 0.001). Moreover, physical education positively influenced social support and exercise behavior (β = 0.523, p < 0.001; β = 0.473, p < 0.001). In turn, social support significantly fostered exercise behavior and improved mental health (β = 0.578, p < 0.001; β = 0.277, p < 0.001). Additionally, enhanced exercise behavior positively contributed to better mental health (β = 0.357, p < 0.001).ConclusionPhysical education is a crucial influencing factor for university students’ psychological health and also indirectly impacts mental well-being through improved social support and increased exercise behavior.